PENANGANAN STUNTING DI DESA LARANGANLOR MELALUI PENYULUHAN DAN CLASS FOODING - Ahmad Zakariya; Annisa' Setyaningsih; Sakti Wahyu Ningsih; Yunika Nurhayati; Nur Hidayatul Mustafidah; Qothrun Nada Salsabila; Rohimah Rohimah; Reza Tri Salamah; Ahmad Irzan; Teguh Setyo Rohmadi; Rochyani Lestiyanawati (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake in infants for a long time starting from pregnancy until the baby is twenty-four months old. Stunting has an impact on the inhibition of mental development, health status, and physical growth in children. In addition, stunting also has an impact on increasing children's vulnerability to diseases, both infectious and non-communicable diseases (PTM). Based on observations in Laranganlor Village, stunting is also caused by the lack of awareness of mothers attending posyandu activities and the emergence of excessive shame when stunting occurs in children. So that public knowledge about the prevention and treatment of children indicated by stunting is very low. However, it cannot be denied that the implementation of a healthy lifestyle and the fulfillment of nutrition for infants is also the reason for the high stunting rate in Laranganlor village. The solution we can offer for this problem is to carry out Stunting Handling Counseling and Class Fooding. By holding this activity, it is hoped that it will have a positive impact on the community and provide changes for the better, especially regarding the importance of maintaining healthy and nutritious food intake for infants in order to prevent stunting